ANALYSIS OF SUSTAINED RICE RECEIVER CUSTOMER SATISFACTION IN SANDAI DISTRICT KETAPANG DISTRICE - Lestari, Ayu; Kurniati, Dewi; Yusra, Abdul Hamid A. (Jurnal Sains Mahasiswa Pertanian, 2019)
The purpose of this study was to analyze the level of customer satisfaction recipients of subsidized rice in Sandai District, Ketapang Regency. The samples used in the study were as many as 100 respondents selected by the purposive sampling method. Data were collected using questionnaires then analyzed by Importance Performance Analysis (IPA) using SPSS 20. Software Important Performance Analysis was used to determine the relationship of importance and performance assessment of the quality of services provided by officers, so they could know what attributes should be improved , maintained, corrected and eliminated or evaluated. Then analyzed again with the Customer Statisfaction Index (CSI) using Microsoft Office Excel to determine the level of customer satisfaction. The results of this study indicate that recipients of subsidized rice are satisfied with the distribution of subsidized rice in Sandai Sub-District, Ketapang District, but it is expected that officers can continue to increase the satisfaction of consumers receiving subsidized rice.Â Keyword: Consumer Satisfaction, Ketapang Regency, Subsidized Rice.